The Taxing Deed of Globalization - Peter Egger; Sergey Nigai; Nora Strecker (Luxembourg Income Study (LIS), 2016)
We examine the effects of globalization on the size and composition of tax revenues, worker-specific tax burdens, and effective average labor income tax rates using a unique international database on income tax calculators. We find that due to increasing mobility of firms and high-income workers, globalization led governments in OECD countries to seek tax revenues from alternative sources, specifically from employee-borne taxes paid by relatively less mobile middle-income workers. In 1994-2007, they experienced a globalization-induced rise in their personal income tax rate of around 1.5, whereas the top 1% of workers faced a reduction of approximately 1.5 percentage points.
Keywords: F1; F6; H2; H3; 330; Globalization; Income taxes; Tax progressivity; International trade; Migration; Einkommensteuer; Lohnsteuer; Steuerbelastung; Mittelschicht; Globalisierung; Multinationales Unternehmen; Brain Drain; OECD-Staaten; Welt